The Application of an Unplugged and Low-Cost Children's Coding Education Tool in a Gamification Context. - Lei Wang; Miao Huang; Ismail@Kamal, Julina (Pertanika Journal of Social Sciences & Humanities, 2024)
Coding education has become a compulsory course for cultivating children's computational thinking, and its tools in a gamification context can further enhance children's learning enthusiasm. Through the literature review, the researchers identified gamification, unplugging, and low cost as important design requirements for children's coding education tools. In order to verify the effectiveness of teaching design, this study specially developed a gamified coding education tool, "Coding Adventure," which allows child learners to take on gamified roles in real-life scenarios and use instruction cards to complete tasks. While testing the prototype in the on-site teaching environment, the researchers invited 12 kindergarten and elementary school teachers to observe the testing process. Then, they formed a focus group discussion to obtain their feedback on the education tool using MAXQDA software for qualitative analysis. According to the results, teacher participants generally recognize the design concepts of gamification, unplugging, and low-cost, and believe that role-playing and rewards in gamification, as well as the use of safe and simple materials to match the existing teaching environment of the school, are successful design innovations. In addition, gamified storytelling has also been proven to enhance students' team communication using this prototype. Overall, this study proves the effectiveness of the design concepts of gamification, unplugged and low cost on the perceived usefulness and ease of use of the coding education tool system under the Technology Acceptance Model theory framework. These studentcentered design concepts will provide valuable experience for the further development of unplugged coding education tools.